(untitled) (The Review of Diabetic Studies, 2025)
Jejunal diverticula are uncommon outpouchings of the small intestine. It is usually asymptomatic and discovered accidently during surgery or imaging investigations. However, in fewer cases, some symptoms were reported. Symptomatic and complicated patients need long-term follow-up to discover recurrence and evaluate treatment efficacy. This is a case of a 72 years old female patient presented to the emergency department (ED) with generalized abdominal pain started 3 days ago, cramping, not radiating, aggrevated by eating food and not relieved by any mean, and associated with non-projectile vomiting. Comuterized tomography (CT) of the abdomen and pelvis with intravenous and oral contrast showed findings suggest a combination of inflammatory and degenerative changes affecting multiple organ systems. Patient went for emergency laparotomy and findings revealed ischaemic segment around in distal jejunum with 2 diverticule in jejunum.